Muzakki’ Preferences and Relevant Factors in Padang - Yuskar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Andalas, 2023)
This paper explores muzakki’ preferences in Padang and describes the existing conditions of some relevant factors that need to be considered (i.e. religiosity and zakat awareness of zakat payers; trust on zakat institutions and perception on governance of zakat institutions). This research was exploratory and descriptive in nature. Data was collected through an online survey involved 123 respondents in 11 sub-districts in Padang during the period of September – October 2020. The findings of the study show that muzakki in Padang have a considerably high religiosity and zakat awareness. The trust to zakat institution, however was only moderate which related to considerably low perception on governance of zakat institutions in Padang. High education and high zakat awareness did not necessarily lead to complete compliance to the recommended zakat payment method (i.e. through authorized zakat institutions). In fact, Muzakki in Padang still used both channels: zakat institutions and direct payment to individual recipients. The findings of this study suggested that more need to be done by zakat institutions to improve governance quality, to socialize their existence and programs to wider groups of society. The research also indicates that preference of zakat payers to pay zakat through online method increases since the Covid-19 pandemic.